Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Mie Gacoan Cabang Magelang - Nuraini, Firda; Novitaningtyas, Ivo (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
In this modern era a lot of progress in the business world. The competition is so tight that every manufacturer continues to develop its business to win the competition. The purpose of the study was to analyze the effect of price and service quality on consumer purchasing decisions at Mie Gacoan Magelang branch. Quantitative methods are used in this study by utilizing primary data from questionnaires distributed to consumer respondents from Mie Gacoan Magelang branch. The sample used was 100 respondents based on the purposive sampling method. Data analysis methods, namely descriptive statistics, coefficient of determination, correlation coefficient, significant F test, and significant t test. The results showed that the perception of price and service quality had a simultaneous influence on purchasing decisions. The results have implications for Mie Gacoan to make efforts to increase consumer purchasing power by lowering prices and increasing promotions for the products offered. From the results of this study, it can be used as a reference for further researchers by developing the variables studied and adding populations and samples to develop the research.